Portable wireless node design for smart agricultural system based on Internet of Things - Al Tahtawi, Adnan Rafi; Andika, Erick; Harjanto, Wildan Nurfauzan (Institute of Advanced Engineering and Science, 2021)
This paper presents a pair of portable wireless nodes for a smart agricultural system to control and monitor the agricultural parameters based on Internet of Things (IoT). This system utilizes low-cost wireless communication through an nRF24L01 module between the sensor node and the controller node. The sensor node is placed on the agricultural area with a Li-Ion battery as a power supply, while the controller node is placed at the control and monitoring station. On the sensor node, there is a YL-69 soil moisture sensor and DS18B20 temperature sensor, while in the controller node there is a relay that can set watering on/off condition. In the controller node, there is also an ESP8266 WiFi module that serves to send data to the internet cloud for user monitoring. Both hardware nodes are built in small and portable size. The experimental result shows that the sensor node can transmit soil moisture and temperature data via RF wireless communication to the controller node. Watering is done automatically based on the condition of sensor values. In addition, this system can also be monitored through a website interface, so the users can easily find out the condition of their plant as long as there is internet access.